Mzala Nxumalo, leftist thought and contemporary South Africa
1 online resource (xviii, 389 pages).
Keywords: Written as a tribute to the revolutionary intellectual and leader Mzala Nxumalo, this book discusses the significance of his work in the context of contemporary South African left politics. It explores the history and struggle of the apartheid era that preceded the advent of democracy to analyze a crucial aspect of the national question - that is, the quest for the establishment of a united South Africa to overcome racist and sexist policies that create and nurture divisions among black people. The subjects in this book deal with a wide range of topics, including the new social, economic and political challenges facing democratic South Africa; the need to reexamine the critique of capitalism in the 21st century; the relationship between race, class and community struggles; and the ecological challenges under capitalism. Print edition not for sale in Sub Saharan Africa